Spatial-temporal variation of Paralonchurus brasiliensis (Actinopterygii: Sciaenidae) density in relation to some environmental factors on the inner shelf of south-eastern Brazilian coast - dos Santos Costa, Eudriano Florencio; Teixeira, Gustavo Monteiro [UNESP]; de Morais Freire, Fulvio Aurelio; Fransozo, Adilson [UNESP] (Cambridge University Press, 2012)
The temporal and spatial variation of Paralonchurus brasiliensis density (fish per m(2)) in relation to environmental factors was studied on the coasts of Ubatuba and Caraguatatuba, south-eastern Brazil. The fish were collected by shrimp fishery trawl on a monthly basis from January to December, 2002. Seven depths were previously established and for each one the temperature, salinity, organic matter content and grain size of the sediment (phi) was measured. The seasonal analysis of temperature and salinity indicated the presence of the water masses South Atlantic Central Water (SACW) and Coastal Waters (CW) acting in the study area. A total of 29,808 fish were collected during the study period. The highest densities were registered during the summer and autumn indicating an association with CW. The fish population moved to shallow depths during the intrusion of the cold water mass, SACW. The highest densities were registered in depths where the sediment composition ranged from fine sand to silt-clay. Thus, the temperature and type of the sediment are the main environmental factors which affect the spatial-temporal variation of P. brasiliensis density in south-eastern Brazil.
Keywords: banded croaker; density variation; environmental factors; south-eastern Brazil